Supporting Merdeka Belajar Curriculum: An Analysis of Open Educational Resources Policy and Academic Libraries’ Contribution - Heriyanto, Heriyanto; Sirait, Yohanes Hermanto (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
In 2023, the Indonesian government launched the Merdeka Belajar (Freedom of Learning) curriculum to enhance the quality of education in the country. College libraries, as integral components of Indonesia's educational system, were called upon to support this initiative, particularly through the use of Open Educational Resources (OER). However, the development and implementation of OER encountered several challenges, including legal barriers. This study aimed to analyze the legal framework surrounding OER, with a particular focus on the Indonesian context. A mixed-methods approach was employed, involving the analysis of legal documents, policies, and relevant literature. The legal documents examined primarily included regulations pertaining to higher education, copyright laws, and licenses. The study found that the lack of specific regulation regarding OER in Indonesia created challenges in defining the applicable legal framework. Although OER practices align with copyright law, the absence of explicit regulation on open licenses places the legal basis on license agreements between creators or copyright holders and OER users. If the license agreement is valid, it becomes enforceable under the pacta sunt servanda principle. However, the study highlighted the need for comprehensive regulations to provide legal security and clarity for creators, copyright holders, and users of OER. It was recommended that the government issue more explicit legal regulations to support the creation, distribution, and use of OER, thereby providing a solid legal foundation for stakeholders, including lecturers, universities, and libraries.